2019
DOI: 10.1021/acscatal.9b02471
|View full text |Cite
|
Sign up to set email alerts
|

Induction Heating: An Enabling Technology for the Heat Management in Catalytic Processes

Abstract: This perspective illustrates the electromagnetic induction heating technology for a rational heat control in catalytic heterogeneous processes. It mainly focuses on the remarkable advantages of this approach in terms of process intensification, energy efficiency, reactor setup simplification, and safety issues coming from the use of radio frequency heated susceptors/catalysts in fixed-bed reactors under flow operational conditions. It is a real enabling technology that allows a catalytic process to go beyond r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
133
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(144 citation statements)
references
References 84 publications
0
133
0
Order By: Relevance
“…Importantly, in situ infrared thermography was employed to examine the surface temperatures and development of hotspots due to the exothermicity of the reaction on structured catalysts based on different foams, showing that both SiC and aluminium foams (with the intrinsically high thermal conductivity) presented the improved heat transfer than alumina foams. In addition, electromagnetic induction heating was applied to regulate heat transfer in structured catalysts (e.g., Ni supported on carbon felt) for catalytic CO 2 methanation process, being able to improve heating/cooling rates with uniform heating environments and high energy efficiency 24‐28 …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, in situ infrared thermography was employed to examine the surface temperatures and development of hotspots due to the exothermicity of the reaction on structured catalysts based on different foams, showing that both SiC and aluminium foams (with the intrinsically high thermal conductivity) presented the improved heat transfer than alumina foams. In addition, electromagnetic induction heating was applied to regulate heat transfer in structured catalysts (e.g., Ni supported on carbon felt) for catalytic CO 2 methanation process, being able to improve heating/cooling rates with uniform heating environments and high energy efficiency 24‐28 …”
Section: Introductionmentioning
confidence: 99%
“…Magnetic induction has recently appeared as an alternative heating source for heterogeneous catalytic reactions . It consists in applying high‐frequency alternating magnetic fields to ferromagnetic materials to release heat through hysteresis losses.…”
Section: Figurementioning
confidence: 99%
“…Magnetic induction has recently appeared as an alternative heating source for heterogeneous catalytic reactions. [1][2][3][4][5][6][7][8][9] It consists in applying high-frequency alternating magnetic fields to ferromagnetic materials to release heat through hysteresis losses. The target temperature is reached within few seconds and the energy is directly transferred inside the material without the need for heating the whole reactor system.…”
mentioning
confidence: 99%
“…7,8 In recent years, we have added inductive heating 9 to the existing portfolio of enabling technologies in organic chemistry 10 and have shown that it can be ideally combined with fluid dynamics to create high-temperature and high-pressure conditions. 11 First studies on sigmatropic rearrangements under flow conditions in organic solvents at 240 °C were described by us. 12 We also demonstrated that water can be heated to near supercritical conditions under fluid dynamics conditions, for example, as a solvent in the continuous synthesis of the atypical antipsychotic drug iloperidone.…”
Section: Scheme 1 the Claisen Rearrangement Of Allyl Arylethermentioning
confidence: 99%